Conjugated polymer single crystals and nanowires. Issue 3 (18th March 2019) - Cao, Xinxiu; Zhao, Kefeng; Chen, Liang; Liu, Jiangang; Han, Yanchun
Abstract : Conjugated polymer single crystals and nanowires show advantages for the study of intrinsic charge transport in conjugated polymers and achieve high device performance. However, preparation of conjugated polymer single crystals and nanowires, especially donor‐acceptor (D‐A) conjugated polymers, is challenging. In this review, the structural features of conjugated polymers are first described. Then, the mechanism of conjugated polymer crystallization in terms of thermodynamic equilibrium state, nucleation, and growth is discussed. Single crystals of poly(alkylthiophene)s (P3ATs) and nanowires of both P3ATs and D‐A conjugated polymers are subsequently reviewed. Growth kinetics are a key issue in growing D‐A‐conjugated polymer crystals. Finally, the device performance based on conjugated polymer single crystals and nanowires is summarized. Abstract : Conjugated polymers have many potential applications for preparation of organic optoelectronic devices. The structural features of conjugated polymers can be divided into two aspects: interchain interactions and backbone stiffness. Here, the authors review the preparation, structure, and device performance of conjugated polymer single crystals and nanowires. The purpose of this review is to summarize the research status of conjugated polymer single crystals and nanowires, as well as to note the difficulties in growing donor‐acceptor conjugated polymer crystals.